Effect of fruit maturity on the composition of high-value components and biological activities of olives from newly developed cultivars - Ullah, Sami; Anwar, Farooq; Rehman, Muhammad Fayyaz Ur; Qadir, Rahman; Ansar, Muhammad Ramzan; M. Ali, Hayssam; Muhammad Mustaqeem; Silva Dias, Ca´ssio da (Elsevier, 2023)
The present study evaluates the variations in the composition of targeted high-value components (phenolics, fatty acids, organic acids and natural sugars) and biological activities of olive fruits, collected at different maturity stages, from two locally developed cultivars BARI Zaitoon-1 (BZ1) and BARI Zaitoon-2 (BZ2). Ultrasound-assisted extraction (UAE) was employed to extract phenolic compounds. The oil yield was significantly increased during the maturation, while a decrease in bioactives extract yield was noted. The maximum oil yield (33.8 %) was recovered from BZ1 olives at the fully ripen stage, while the maximum extract yield (34.5 %) was given by BZ2 at the unripen stage. According to HPLC analysis, total phenolic acids, including sinapic, caffeic, gallic, chlorogenic and benzoic acids in BZ1 and BZ2 olives, were higher at semi-ripen and unripen stages, respectively. Myricetin was detected as the major flavonoid in both cultivars, but its concentration gradually decreased during fruit maturation. A good correlation of total phenolic contents (TPC) with 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging and total flavonoid contents (TFC) with ferric reducing antioxidant potential (FRAP) was observed. Similarly, an increase in the contents of total sugars and organic acids was noticed corresponding to fruit maturity. Furthermore, the tested olives fruit extracts inhibited the growth of Gram-positive bacterial strains (B. subtilis and S. aureus) more effectively than Gram-negative strains (K. oxytoca, S. typhi, and E. coli). The GC–MS analysis of extracted olive oil revealed that oleic acid was the major fatty acid found at three maturity stages for both cultivars. The current research revealed considerable variations in the selected components profile and biological activities of the tested olive cultivars as a function of fruit maturity. Based on these findings, the uses of olives can be recommended for specific applications to maximize the functional food and nutraceutical benefits of this valuable fruit.